The Effect of The GeoGebra-Based Project Based Learning (PjBL) Model on the Creative Thinking Ability of Junior High School Students - Wiyanti, Adella Irma; Hadi, Windia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The PjBL model provides opportunities for individuals to work freely, which fosters genuine individual creativity and the ability to think creatively using media such as GeoGebra. GeoGebra media is able to visualize in a realistic manner, allowing individuals to understand it effectively. This study aims to determine the effect of the GeoGebra-based Project Based Learning (PjBL) model on the creative thinking skills of junior high school students. This is quantitative research using a quasi-experimental approach with a posttest-only control design. The sample of this study are 70 seventh-grade students, particularly 35 students for the ability to think creatively in the GeoGebra-based PjBL model and 35 for the Non-GeoGebra-based PjBL model. The instrument employed consisted of a 5-question essay test on the ability to think creatively, with earlier phases of the validation of expert and from the eighth-grade students in various schools. The results of data analysis using the Mann Whitey Non-Parametric test were obtained at 0.118 (P Value > 0.05 significant level). According to the findings of the analysis, the GeoGebra-based PjBL model does not significantly convert the creative thinking abilities of the students, despite it gives an impact of the influence of junior high school students' abilities.